Genome-Wide DNA Methylation Profiles Reveal Common Epigenetic Patterns of Interferon-Related Genes in Multiple Autoimmune Diseases - Chen, Sidi; Pu, Weilin; Guo, Shicheng; Jin, Li; He, Dongyi; Wang, Jiucun (Frontiers in Genetics, 2019)
Graves’ disease (GD), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are complex autoimmune diseases sharing common clinical, genetic and pathogenetic features. However, the commonalities of the DNA methylation profiles for these diseases are still unknown. We conducted an integrative analysis of the multiple-autoimmune disease methylation dataset including GD, RA, SLE and SSc samples, to identify the common methylation patterns of autoimmune diseases. We identified 15,289 differentially methylated sites between multiple-autoimmune disease patients and controls in CD4+ T cells. We found that the most significant differentially methylated sites had a remarkable enrichment in type I interferon (IFN) pathway genes. Similarly, we identified 9,295 differentially methylated sites between GD/SSc patients and controls in CD8+ T cells. The overall IFN-related gene panel annotated by gene ontology (GO) showed an excellent diagnostic capacity in CD4+ T cells (Sensitivity=0.82, specificity=0.82 and AUC=0.90), while IFI44L, another IFN-related gene not annotated by GO, showed high prediction ability in both CD4+ (AUC=0.86) and CD8+ (AUC=0.75) T cells. In conclusion, our study demonstrated that hypomethylation of IFN-related genes is a common feature of GD/RA/SLE/SSc patients in CD4+ T cells, and the DNA methylation profile of IFN-related genes could be promising biomarkers for the diagnosis of GD, RA, SLE and SSc.